Influência do tamanho de partículas do fosfato de Araxá sobre a disponibilidade de fósforo para híbridos de sorgo - Quintâo Lana, Regina Maria; Braga, José Mário; Ribeiro, Antônio Carlos; Lima Thiébaut, José Tarcísio; Lima Neves, Júlio César (Revista Ceres, 2025)
Greenhouse studies were conducted to study the effect of nine Araxa rock phosphate granulometries and two phosphorus (P) levels, in the presence and absence of lime, o P availability for two sorghum hybrids.